Ortho-surgical procedure involving mandible, maxilla, mento and associations: a systematic review - Velez Avendaño, Gabriel Rodolfo (2022)
Introduction: Orthognathic surgery (OS) consists of the surgical procedure that aims to correct deformities of the bones of the maxilla and mandible. The records of the first surgeries for the correction of dentofacial deformities date from the mid-nineteenth century and were initially limited to mandibular surgeries. The malocclusion has as one of the primary etiological factors the facial growth pattern. Angle's statement already said that the only possibility of correcting true dentofacial deformities was the combination of orthodontics with surgery, and the importance of the combined effort of these two distinct areas in the approach to dentofacial disharmony in patients with problems was recognized skeletal. Objective: This study aimed to review the literature on OS involving mandible, maxilla, mento and associations. Methods: Clinical studies with qualitative and/or quantitative analysis were included, following the rules of the systematic review-PRISMA. Results: A total of 107 articles were found involving “orthognathic surgery". A total of 47 articles were evaluated in full, and 33 were included and discussed in this study. Individuals with class III dentofacial deformities are those that normally present greater aesthetic and functional impact, and for this reason, are the ones that more frequently seek treatment. However, some studies have shown a tendency for complications to occur in older patients submitted to orthognathic surgeries. Mandibular surgical procedures with maxillary segmentation and combining three types of osteotomies should be carefully planned and trained to reduce the occurrence of complications. The surgeon, orthodontist, and all staff involved should be focused on avoiding complications during all phases of treatment. Conclusion: It was concluded that there was an increase in the cases of OS in the last years, and with homogeneous samples between the masculine and feminine genres, and the advances in maxillary surgery corresponded to the greater number of surgical treatments.